(untitled) (Bioscience Journal, 2016)
The droplets population and spectrum produced during a spraying influence the pesticides distribution efficiency. Through the droplets population and spectrum is possible to determine the quality of spraying and the implications on applicator and consumer safety, application efficiency and environmental impact. Droplet density (droplets cm-2), percentage of coverage, coefficient of uniformity and relative amplitude were studied in this experiment. The experimental design was a factorial scheme 3 x 2: three spray volumes and two insecticides doses. During the tests all factors were analyzed on six parts of the plant canopy: on the top and external, top and internal, middle part and external, middle part and internal, bottom and external, and bottom and internal, using the completely randomized design with three replications. The objective of this study was to assess the characteristics of droplets population and spectrum produced during the hydraulic spraying. In general, for all factors assessed there was no significant difference between the parts of the plant canopy studied, having the greater values on the external parts of the plant canopy.